Management of Strengthening Pancasila Values within the Merdeka Curriculum to Foster Civic Disposition in Madrasah Ibtidaiyah - Subar Junanto; Mila Faila Shofa; Putri Rizqiyah Rahmawati; Latifah Permatasari Fajrin (CV Edujavare Publishing, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in strengthening Pancasila values to develop students’ civic disposition at MI Muhammadiyah Klaseman Gatak Sukoharjo. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving the head of the madrasah, teachers, the coordinator of the Pancasila Student Profile and Rahmatan lil ‘Alamin Student Profile Project (P5 P2RA), and students as research information sources. The analysis focused on the integration of Pancasila values through intracurricular learning, madrasah culture, character-building activities, and P5 P2RA projects within the implementation of the Merdeka Curriculum. The findings reveal that the strengthening of Pancasila values at MI Muhammadiyah Klaseman Gatak Sukoharjo is carried out through an educational ecosystem involving madrasah leadership, teacher roles, student participation, and school environmental support. The implementation process is managed through the management functions of Planning, Organizing, Actuating, and Controlling (POAC), which are reflected in aligning the madrasah vision, organizing collaboration among school members, implementing learning activities and madrasah culture, and conducting continuous evaluation of students’ character development. Values such as responsibility, mutual cooperation, tolerance, social awareness, and respect for diversity develop through contextual learning experiences embedded in students’ daily activities at the madrasah. This study concludes that the implementation of the Merdeka Curriculum provides a strategic opportunity for Islamic-based madrasahs to integrate national values and religious values in developing students’ civic disposition. The contribution of this study lies in understanding how the management of the madrasah ecosystem through the POAC perspective can support the systematic and sustainable implementation of Pancasila values in Islamic elementary education